2012
DOI: 10.1103/physrevlett.109.228002
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Surface Tension in Vibrated, Noncohesive Granular Media

Abstract: We describe experiments and simulations carried out to investigate spinodal decomposition in a vibrated, dry granular system. The dynamics is found to be similar to that of systems evolving under curvature-driven diffusion, which suggests the presence of an effective surface tension. By studying quasi-2D droplets in the steady state, we find behavior consistent with Laplace's equation, demonstrating the existence of an actual surface tension. Detailed measurements of the pressure tensor in the interfacial regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
5
28
1
Order By: Relevance
“…The situation is, then, similar to the results of the experiments reported in Refs. [16,17]. For spatially homogeneous situations, the predictions of the equations for the horizontal and vertical temperatures agree very well with MD simulation results for mild inelasticities, both for the stationary values and for the dynamics.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…The situation is, then, similar to the results of the experiments reported in Refs. [16,17]. For spatially homogeneous situations, the predictions of the equations for the horizontal and vertical temperatures agree very well with MD simulation results for mild inelasticities, both for the stationary values and for the dynamics.…”
Section: Introductionsupporting
confidence: 69%
“…Originally, the system is open from above, being gravity the cause of the confinement [12,13]. The system can also be confined by a top lid, the distance between plates being much smaller than the horizontal dimensions in such a way that it can be considered quasi-two-dimensional (Q2D) [14][15][16][17][18][19][20]. The bottom plate is usually smooth, although rough plates have also been used [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both system classify as strongly forced systems for which momentum transfer trough collisions dominates other forces. Nonetheless, low surface tensions-of the order of 1 mN/m-have also been measured in these strongly agitated noncohesive granular systems that phase separate (Clewett et al, 2012;Luu et al, 2013). To our knowledge, these two systems are the only examples that have shown the emergence of an effective surface tension induced by dissipative collisions rather than by low cohesive forces (Royer et al, 2009) or by air drag (Duran, 2001;Amarouchene, Boudet, and Kellay, 2008).…”
Section: Effective Surface Tensionmentioning
confidence: 88%
“…For granular gases, it was found that the coarsening dynamics can indeed be explained by the emergence of a positive non-equilibrium surface tension that is predominately determined by the anisotropy in the kinetic energy part of the stress tensor in contrast to the surface tension in molecular fluids, which is mainly determined by energetic interactions. 12 Another model system that has recently received huge interest is a system of active Brownian particles suspended a) Electronic mail: s.paliwal@uu.nl b) S. Paliwal and V. Prymidis contributed equally to this work. c) Electronic mail: m.dijkstra@uu.nl in a solvent that incessantly converts energy from the local environment into directed motion and is thus inherently outof-equilibrium.…”
Section: Introductionmentioning
confidence: 99%